Optimization and comparison of water degumming and phospholipase C degumming for rapeseed oil. Issue 4 (1st October 2016) - Ye, Zhan; Qiao, Xue; Luo, Zhi; Hu, Chuanrong; Liu, Lingyi; He, Dongping
ABSTRACT: In the present study, the phospholipase C (PLC) degumming and water degumming process were studied, respectively, and each was optimized by orthogonal array experimental design; the minimum phosphorus content of PLC degumming was 7.34 ± 0.39 mg/kg, while that of water degumming was 61.54 ± 1.57 mg/kg. Oxidation stability of different oils were analyzed by testing the induction time, and the induction time of degummed oils were a little shorter than crude oil due to the removal of natural phospholipids which acted as antioxidants. Diacylglycerol and triglyceride analysis results showed that PLC degumming was superior to water degumming in increasing the oil yield and decreasing the neutral oil loss during the degumming process. According to the phospholipids composition analysis of degummed oil gums, it could be concluded that PLC was effective to remove the phosphatidylcholine and phosphatidylethanolamine, while having no activity on phosphatidylinositol or phosphatidic acid.